2010
DOI: 10.1038/aja.2010.37
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase 2 gene polymorphisms are associated with prostatic volume in Korean men with benign prostatic hyperplasia

Abstract: The precise aetiology of benign prostatic hyperplasia (BPH) remains unclear; however, it is known that immunological inflammatory processes have a role in the pathogenesis of BPH initiation and progression. Nitric oxide synthase 2 (NOS2) inducible expression is closely correlated with prostatic disease, including prostate cancer and BPH. The aim of this study was to investigate the relationship between NOS2 polymorphisms and BPH. With a cohort of 205 controls and 229 BPH subjects, we genotyped three single nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
(32 reference statements)
0
12
1
Order By: Relevance
“…The aim of the present study was to investigate whether four single nucleotide polymorphisms (SNPs) (rs4986938, rs17766755, rs12435857 and rs1256049) of the ESR2 gene were associated with the development of BPH. Based on their symptoms, the subjects were allocated to either the control (prostate volume, <30 ml) or the BPH [prostate volume, ≥30 ml; IPSS, >8; Qmax, <15 ml/sec] group (11,12). The demographic characteristics of the BPH and control groups are shown in Table I.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study was to investigate whether four single nucleotide polymorphisms (SNPs) (rs4986938, rs17766755, rs12435857 and rs1256049) of the ESR2 gene were associated with the development of BPH. Based on their symptoms, the subjects were allocated to either the control (prostate volume, <30 ml) or the BPH [prostate volume, ≥30 ml; IPSS, >8; Qmax, <15 ml/sec] group (11,12). The demographic characteristics of the BPH and control groups are shown in Table I.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that ETS-1 represses the expression of the immunity-related genes CD38 and HDAC9, while activating the expression of BCL11A, CRISP3, DMBT1, FGR, NOS2 and SAA1 in PC3 PCa cells. Besides the roles of these genes in the immune response, several have been reported to be involved in various types of cancer, including PCa (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). However, the precise roles that these genes may play in the network of cellular and molecular mechanisms of antitumor immunology according to current models is not always clear from the literature.…”
Section: Discussionmentioning
confidence: 70%
“…FGR has been suggested to play a significant role in ovarian carcinoma cancer growth (25). NOS2 has been reported to be implicated and correlated with various prostatic diseases including PCa (26). Finally, SAA1 has been found to be highly expressed in lung cancer tissue (27) and over-expressed in ovarian carcinoma tissues (28).…”
Section: Discussionmentioning
confidence: 99%
“…Benign prostatic hyperplasia (BPH) is a pathological change that causes lower urinary tract symptoms and is one of the most common urologic diseases in older men (Yoo et al, 2010;Huh et al, 2013). Studies from western countries have reported that the prevalence of BPH is 40-50% by age 50 years and nearly 80% by age 70 years (Burnett and Wein, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Some research has shown that inflammatory cytokines, such as interleukin (IL)-2, IL-7, and interferon-γ, are overexpressed in BPH tissue (Kramer et al, 2002). Furthermore, recent studies have shown that nitric oxide synthase 2, IL-10, and IL-10RB gene polymorphisms are associated with BPH (Yoo et al, 2010(Yoo et al, , 2011. Lymphotoxin (LT), which was first identified in 1968, is a cytotoxic molecule produced by lymphocytes.…”
Section: Introductionmentioning
confidence: 99%